Propuesta de evaluación del desempeño docente para el colegio nacional San Pablo de Otavalo - Orbe Cárdenas, Luis Fernando (2011)
The performance appraisal is an important factor in raising educational quality. Current educational practices require teachers with a high level of professional development, capable of facing new challenges and changes in society. In the educational context Ecuadorian resistance to change, apathy, a weak sense of belonging, dissatisfaction with the styles of teaching evaluation, among other things, a negative impact on the successful performance of teachers in service and quality educational.